Implementasi Teknik Penilaian Proyek dan Penilaian Sejawat Untuk Menilai Kompetensi Menulis Proposal Siswa Kelas XI SMA Negeri Karangpandan - , Aminatun; , Laili Etika Rahmawati, S.Pd., M.Pd (2017)
The purpose of this study was to determine the execution and implementation of the project assessment and peer assessment in the teaching of writing of student XI grade of SMA Karangpandan. This type of research is qualitative descriptive. Data collection techniques used were observation, interviews, tests, and documentation. Data analysis technique used is data reduction, data presentation, and draw conclusions and verification. It can be concluded that (1) In the assessment of the project planning process, teachers carry out the four stages, namely the determination and dissemination of matter, the preperation of grating, and the formulated of indicators about the items test. Through the project assessment could be done an assessment of the specific skills and knowledge in the context of which require the application of a more general skills (process of the project and the final product). Project work is used by teachers to assess students on work and working time doing other projects are best used to assess the final product. (2) Implementation of peer assessment to assess the write competence of the students grade XI of SMA Karangpandan consists of three stages, namely peer assessment planning, implementation attitude assessment through self-assessment and feedback. Keyword: project assessment, peer assessment, writing competence